Efficacy of a vermifilter at mitigating greenhouse gases and ammonia emissions from dairy wastewater. Issue 4 (22nd June 2022) - Miito, Gilbert J.; Ndegwa, Pius M.; Alege, Femi P.; Coulibaly, Sifolo S.; Harrison, Joe
Abstract: Dairy effluent is a potential source of gaseous pollutants associated with global warming and soil acidification. Mitigating such emissions during handling and storage requires substantial financial and labor input. This study evaluated a low‐cost technology for mitigating gaseous emissions from dairy wastewater. For 9 mo, a pilot‐scale vermifilter system installed on a commercial dairy farm was studied. Bimonthly samples of the dairy wastewater influent and effluent from the vermifilter system were collected. These samples' potential gas emissions (ammonia [NH3 ], methane [CH4 ], carbon dioxide [CO2 ], and nitrous oxide [N2 O]) were measured using a closed‐loop dynamic flux chamber method. Results indicated the following reductions in emissions of these gases by the vermifilter system: 84–100% for NH3, 58–82% for CO2, and 95–100% for CH4 . Nitrous oxide emissions were mainly below our instrument detection limits and were thus not reported. The vermifilter showed the potential of reducing the global warming potential from the dairy wastewater by up to 100%. This study further indicated that higher ambient temperatures led to higher emissions of CH4 ( R 2 = .56) and NH3 ( R 2 = .53) from untreated dairy wastewater. Overall, the vermifilter system has potential to mitigate gaseous emissions from dairy wastewater. Core Ideas: The vermifilter system reduced wastewater gas emissions (NH3 = 100%; CH4 = 100%; CO2 = 82%). The vermifilter system reduced potential GHG emissions from dairy wastewater by up to 100%. Temperature significantly increased CH4 (56%) and NH3 (53%) emissions from untreated wastewater. The vermifilter system's carbon footprint was significantly low (<2 kg CO2 ‐eq d −1 ).